2016
DOI: 10.3319/tao.2015.10.28.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Tides and Typhoon Fanapi (2010) on Seas Around Taiwan

Abstract: We used satellite data, typhoon-resolving atmospheric forcing and a data assimilating ocean model, the East Asian Seas Nowcast/Forecast System (EASNFS), to investigate circulation and three upwelling regions perturbed by tides and Typhoon Fanapi (2010) in the seas around Taiwan. The three upwelling areas located off northeast Taiwan, off southeast China and over the Penghu Channel off southwest Taiwan are normally limited in expanse before Fanapi. The tidal currents enhance all three. To cope with typhoon stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…In addition, typhoon Roke was formed southeast of Taiwan on July 21 and traveled northwest and passed through the Luzon Strait, reaching Hong Kong on July 23. The typhoon might have induced upwelling, and the upwelling may have been enhanced by the cyclonic vorticity (Ko et al, 2016). Southwesterly winds changed direction after October (Figure 2), which may have slowed down the northward flow and upwelling.…”
Section: Water Masses Variety and Nutrients Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, typhoon Roke was formed southeast of Taiwan on July 21 and traveled northwest and passed through the Luzon Strait, reaching Hong Kong on July 23. The typhoon might have induced upwelling, and the upwelling may have been enhanced by the cyclonic vorticity (Ko et al, 2016). Southwesterly winds changed direction after October (Figure 2), which may have slowed down the northward flow and upwelling.…”
Section: Water Masses Variety and Nutrients Availabilitymentioning
confidence: 99%
“…Jan et al (2010) revealed three primary water masses in the Taiwan Strait: the Kuroshio Branch Water (KBW) with high temperature and high salinity, the Mixed China Coastal Water (MCCW) with low temperature and low salinity, and the South China Sea Water (SCSW) with intermediate temperature and salinity. Additionally, tropical storms and typhoons also influence this area during the summer via induced heavy rainfall, strong vertical water mixing or upwelling (Ko et al, 2016). Jan et al (2002) pointed out that the deep Penghu Channel guides the intruding KBW northward into the Changyun Rise (CYR) and partially blocks along-strait transport on the eastern side of the strait in winter.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the model domain 142 rivers derived from the World Meteorological Organization Global Runoff Data Center archives were included with monthly climatologic mass flux, temperature and zero salinity from their respective river mouths. The preliminary numerical experiments noted the importance of tides in driving enhanced upwelling in the seas around Taiwan and ECS so eight tidal constituents (K1, O1, P1, Q1, K2, M2, N2, and S2) were included (Ko et al, 2016). These were obtained from the Oregon State University Tidal Prediction Software (Egbert and Erofeeva, 2002).…”
Section: Model Descriptionmentioning
confidence: 99%
“…To examine the impact of large scale circulation on coastal currents during typhoons, it is possible for our model to use the results from the large scale ocean circulation model (e.g., Ko et al 2016) as open boundary conditions.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…While this study focues on the storm surge, waves, and inundation induced by Fanapi and Soulik around Taiwan, a recent study by Ko et al (2016) studied the impact of Fanapi and tides on coastal upwelling and circulation around Taiwan. Their study found that, on its way to Taiwan, Fanapi induced a cold wake spreading preferably on the right side of the essentially westward running track in the western Pacific.…”
Section: Introductionmentioning
confidence: 99%